KLASIFIKASI SENTIMEN MAGANG MERDEKA BELAJAR MENGGUNAKAN ALGORITMA KNN - Hollywrit Travaganz Nainggolan (2022)
On 2020, Indonesian Ministry of Education and Culture launch a program called Merdeka Belajar: Kampus Merdeka, this program consists of internships, independent study, and student exchange. However, in case of internships, this program sparks controversy since the participants share their experiences during the internship program by Magang Merdeka. Author are interested to do research on this sentiment by classifying it as either positive or negative sentiment. One of the preferred method is by using KNN algorithm. Author is using KNN since it is the easy-to-use and reliable algorithm out there. The final purpose is to classifying the sentimen ton Kemendikbud's program, whether it's more received or not.